Histological Studies in Murine Model of Asthma: Effect of Stat3 siRNA - Bhushan Chaudhari, Pankaj Jagdale, Sheikh Raisuddin, Shambhoo Sharan Tripathi, Mamta Shukla, Pradeep Kumar Singh, Pradeep Kumar (Journal of Applied Pharmaceutical Science)
Airway remodeling in asthma is recognized as irreversible structural change. However, several recent reports revealed that remodeling might be the process of repair from injury. Airway remodeling is increasingly recognised to be a serious consequence of chronic asthma.Stat3 and Cytokines play an integral role in the coordination and persistence of inflammation. However, exact role of Stat3 in airway inflammation is lacking. In the present study BALB/c mice were sensitized and challenged with OVA (OVA/OVA) after validation these mice models were further studied to check silencing effect of Stat3 .mRNA and ELISA studies revealed alteration in IL-4, IL-5, IL-13 and TGF-β in BALF and lung with blood eosinophilia also airway hyperresponsiveness in OVA/OVA mice. Airway hyperresponsiveness was studied by methacholine-induced specific airway resistance in a plethysmogrpah while eosinophils study was done using automatic blood analyser. Total and OVA-specific IgG and IgE antibodies depicted significant rise among mice sensitized and challenged with OVA. Studies pertaining to histology revealed fibrous tissue proliferation along with other inflammatory changes in airway structure among OVA/OVA mice and it are the characteristic of human model of asthma. Heightened expression of TGF-β and proliferation of fibrous tissue in lungs are directly related. On the contrary SAL/SAL mice revealed normal blood eosinophils. There was no change in IL-4, IL-5, IL-13 and TGF-β also OVA-specific IgG and IgE antibodies in SAL/SAL mice presented normal range. Our earlier studies showed downregulation of Stat3 gene in airway tissues is related with airway inflammation in a mouse model of asthma using this background we tried to study airway histology after silencing Stat3 gene in OVA/OVA mice interestingly our results showed that silencing Stat3 did not help in restoring airway histology in OVA/OVA mice in addition to this investigations pertaining to cytokines, immunoglobulins, blood eosinophils, sRAW and mRNA studies did not depicted any sign of restoration.
Keywords: Asthma, Airway remodelling, Cytokines, Stat3, Mice.